2012
DOI: 10.1021/jp309744s
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Structure and Nonlinear Vibrational Spectra of Water Next to Hydrophobic and Hydrophilic Solid Surfaces

Abstract: Molecular dynamics simulations have been used to study the structure of water molecules adjacent to solid hydrophobic and hydrophilic surfaces. The hydrophobic surfaces resemble self-assembled monolayers with methyl termination, whereas the hydrophilic surfaces are terminated with hydroxyl groups. The resulting water structure is characterized by its density profile, order parameters, and molecular tilt-twist distribution as a function of distance from the surface. In both cases, results are compared to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 94 publications
16
32
0
Order By: Relevance
“…Roy et al later applied the same method to study water next to model hydrophilic and hydrophobic surfaces, and produced results that qualitatively matched experimental spectra, accounting for the lack of free OH modes at hydrophilic surfaces. 58 Here we use data from those simulations on hydrophilic OH-terminated surfaces to extract α (2) lmn for interfacial water 10 molecules. The overall goal is to arrive at the hyperpolarizability for a typical 3200 cm -1 species, and also for a 3400 cm -1 species that takes the vibrational mode symmetry, strength of the hydrogen bonding network, and coordination into account.…”
Section: Spectral Intensity Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy et al later applied the same method to study water next to model hydrophilic and hydrophobic surfaces, and produced results that qualitatively matched experimental spectra, accounting for the lack of free OH modes at hydrophilic surfaces. 58 Here we use data from those simulations on hydrophilic OH-terminated surfaces to extract α (2) lmn for interfacial water 10 molecules. The overall goal is to arrive at the hyperpolarizability for a typical 3200 cm -1 species, and also for a 3400 cm -1 species that takes the vibrational mode symmetry, strength of the hydrogen bonding network, and coordination into account.…”
Section: Spectral Intensity Simulationsmentioning
confidence: 99%
“…Details of the molecular dynamics simulations and the preparation of the surfaces have been described previously. 58 From the two uncoupled frequencies ω 1 and ω 2 of each water molecule, we determine the eigenvalues ω high and ω low and corresponding eigenvector…”
Section: Spectral Intensity Simulationsmentioning
confidence: 99%
“…The authors succeeded to separate the contribution of the third-order susceptibility from the intrinsic SFG spectra of charged silica-water interface and obtained an SFG spectrum of a neutral quartz-water interface in a qualitative agreement with that measured by Myalitsin et al 18 for a low pH conditions. Manifestations of hydrophobic/hydrophilic interactions on a solid-water interface were investigated by Roy and Hore 50 . The structure and spectral response of water near a hydrophobic surface mimicked by a methyl-terminated self-assembled monolayer were found to be similar to those of the water-vapor interface, in an agreement with the results by Tyrode and Liljeblad.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the results of previous research on the structure of water near a flat hydrophilic surface. Sandra and Dennis showed that with certain distances from hydrophilic surfaces, the hydration layer exhibits poor H‐bonds compared to bulk water . On the contrary, tetrahedrally ordered water has been reported near the charged residues at a protein surface .…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with the results of previous research on the structure of water near af lat hydrophilic surface.S andra and Dennis showed that with certain distances from hydrophilic surfaces,t he hydration layer exhibits poor H-bonds compared to bulk water. [20] On the contrary,t etrahedrally ordered water has been reported near the charged residues at aprotein surface. [21] Additionally, the size of ions [22] and the topology of al ocal biological surface [23] have been reported to affect the H-bond network of water molecules in ad iverse and complex way.F or example, asmall halide ion rarely perturbs the water network as much as al arge halide ion.…”
Section: Angewandte Chemiementioning
confidence: 99%